O suicídio no conto brasileiro contemporâneo - Rodrigues, Danielle Santos (2015)
This paper aims to analyze the suicidal representations on contemporary Brazilian tales from certain conceptions about contemporaneity. A corpus of twenty tales was gathered by the following writers: Marcelino Freire, Sérgio Sant’Anna, Adriana Lunardi, Lygia Fagundes Telles, Dalton Trevisan, Lucienne Samôr, Antonio Carlos Viana, Nivaldo Tenório, Caio Fernando Abreu, Rubem Fonseca, Marcelo Benvenutti, Nelson de Oliveira, located between the 1970’s and 2012. Through a comparative study between literary text and philosophical, sociological, psychological and political themes, as well as literary theory, a repetition of specific characteristics and themes was perceived. After reviewing literature about suicide, grounded mainly in Durkheim (2000), Camus (2008), Puente (2008), Dias (1991), and Marquetti, (2011), about tales in Cortázar (1974), Poe (1999), Piglia (2004), and Ogliari (2012), and about contemporaneity in Eagleton (1998), Harvey (1992), Jameson (2006a; 2006b), and Lyotard (2013), the literary composition was addressed by using conceptions of parody, metafiction and pastiche, which were treated from Hutcheon (1989; 1991) and Jameson (2006).Then the following themes were analyzed: suicide as sacrifice and ritual, Girard (1998, 2004), Derrida (2005), and Agamben (2007); the spectacularization of suicide, Marquetti (2011), Baudrillard (1995); the (mis)treating of the body when killing oneself, Le Breton (2011); the suicidal as strange and estrangement, Freud (1976), Chklovski (1978), and Ginzburg (2001); the usage of tale as a space of reflection about suicide, Ogliari (2012). This paper was guided on the quest of whether there could be any thematic and/or esthetic stability in this recurrence on the contemporary Brazilian tales that talk about suicidal stories. As hypothesis, we reached the proposition that there could be both a rupture in the moral and religious prohibition, and a reflection of cultural order, represented by the identity and/or otherness of the suicidal, considering that the internal tension in the narrative or between text and reader would be powered by the genre tale and by the way that authors build the plot. Considering the themes and forms they are written, it is possible to conclude that tale and suicidal keep a connected relationship about the gaps left in both, allowing that the genre act, in a more specific way, the silences that involve suicide. This way, tales about suicide gather and carry unique characteristics in the history of the Brazilian literature.